2021
DOI: 10.1590/1678-4324-2021200179
|View full text |Cite
|
Sign up to set email alerts
|

Limonium duriusculum (de Girard) Kuntze Exhibits Anti-inflammatory Effect Via NF-κB Pathway Modulation

Abstract: HIGHLIGHTS L. duriusculum n-BuOH extract reduces inflammatory responses both in vitro and in vivo. L. duriusculum n-BuOH extract inhibits NF-κB-dependent transcriptional responses. L. duriusculum n-BuOH extract decreases the expression of TNF-α and IL-6 genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…As a nuclear transcriptional factor, NF-κB regulates the expression of various inflammation and immune response-related genes [ 32 ]. It can be activated in LPS-stimulated macrophages, followed by the phosphorylation of the repressor protein IκBα and dissociated from NF-κB, leading to NF-κB translocation into the nucleus to induce the expression of inflammatory cytokines genes [ 33 ]. In order to clarify whether LGSP and CO could regulate NF-κB translocation, the nuclear and cytoplasmic fractions were determined by Western blotting analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As a nuclear transcriptional factor, NF-κB regulates the expression of various inflammation and immune response-related genes [ 32 ]. It can be activated in LPS-stimulated macrophages, followed by the phosphorylation of the repressor protein IκBα and dissociated from NF-κB, leading to NF-κB translocation into the nucleus to induce the expression of inflammatory cytokines genes [ 33 ]. In order to clarify whether LGSP and CO could regulate NF-κB translocation, the nuclear and cytoplasmic fractions were determined by Western blotting analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In similar studies of the immunomodulatory effects of Limonium species, it was demonstrated that the polysaccharides of L. sinense improved the phagocyto-sis activity of macrophages in immunosuppressed mice and increased the proliferation and production of IFN-γ and IL-2 by splenocytes in vitro [11]. The extract of L. duriusculum and the isolated flavonoid apigenin inhibited proinflammatory NF-κB-dependent transcriptional responses in HCT116 and THP-1 cells [39]. These observations, as well as the results of the current study, raise the prospect of using the extracts of L. gmelinii and related species for the treatment of diseases associated with immune disorders.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, UAE could have advantages over CE, as it is significantly faster and simpler and has a lower solvent consumption and "greener" approach [27]. The LC-QToF-MS analysis clearly showed impressive compositions of both extracts, rich in biologically active compounds with remarkable immunomodulatory potential, such as apigenin [39], epigallocatechin-3gallate [20] and quercetin [20]. This work reported, for the first time, that extracts from the above-ground parts of L. gmelinii may modulate the inflammatory mode of murine macrophages and lymphocytes via the stimulation or suppression of TNF-α and IL-6 production and splenocyte proliferation depending on the status of these immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some results found in the literature report characteristics in the leaves of different statice species as high contents of flavonoids, vitamin C, total phenolic compounds and antioxidant activity [6][7] . The plant exhibits antiinflammatory and antitumor action [8][9] , and is employed in the treatment of fever, menstrual disorders and colic 5 .…”
Section: Introductionmentioning
confidence: 99%